Perbedaan Mekanisme Penyelesaian Pelanggaran HAM Berat di Aceh dan Daerah Lain di Indonesia - Lala Lala; Rahmiati Rahmiati; Eprina Mawati Br. Siboro (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article analyzes the different mechanisms for resolving gross human rights violations through the Human Rights Court under Law Number 26 of 2000 and the Aceh Truth and Reconciliation Commission under Aceh Qanun Number 17 of 2013. Using normative legal research with statutory and conceptual approaches, it finds that the two mechanisms do not conflict de jure because their powers, procedures and legal outputs are distinct. The Human Rights Court focuses on criminal accountability, whereas the Aceh TRC emphasizes truth-seeking, reparations and reconciliation. De facto, however, they continue to operate in parallel without protocols for data exchange, case referral, witness and victim protection and the implementation of reparations. Integration is scientifically necessary not to homogenize their mandates, but because victims’ rights to justice, truth, protection, recovery and guarantees of non-recurrence are interdependent. Without integration, victims face repeated testimony, data confidentiality risks, disconnected legal referrals and unimplemented recovery recommendations. An integrative model should therefore link the Aceh TRC, LPSK, Komnas HAM, the Attorney General’s Office, the Human Rights Court and government institutions while preserving institutional independence, victims’ consent, confidentiality and due process of law.